Estrus synchronization and superovulation in goats: a review - Abdullah, Ramli; Wan-Khadijah, W.E.; Rahman, A.N.M.A. (2008)
The study was intended to review the recent developments and advances of estrus synchronization and superovulation protocols in goats with a view to improve oocytes/embryo recovery for In Vitro Production (IVP) efficiencies. Although a number of estrus synchronizing protocols has been developed in goat the most widely used one is the treatment of progesterone for 9-11 days followed by a luteolytic dose of prostaglandin administered in the period 48 h prior to removal of intravaginal sponge. Until now, Controlled Internal Drug Release (CIDR) device and subcutaneous implants are more preferable than sponges. Ovulation in goat can be synchronized more precisely by administering Gonadotrophin Releasing Hormone (GnRH) around the time of estrus that improves the success of fixed-time Artificial Insemination (AI) and oocytes or embryos collection at a controlled stage. Superovulation is the hormonal treatment for increasing a large number of oocytes that ultimately accelerate genetic improvement in any species. Generally an exogenous follicle-stimulating gonadotrophin is administered that mimics the effect of Follicle Stimulating Hormone (FSH) near the end of the luteal phase of the cycle (9-11 days) or around 48 h before the end of the synchronizing treatments. The major commercial products applied are equine Chorionic Gonadotrophin (eCG) or Pregnant Mare Serum Gonadotrophin (PMSGT) and FSH. This review paper describes estrus synchronization, ovarian superovulation as well as the normal physiology of estrous cycle and ovulation in goats. © 2008 Asian Network for Scientific Information.